Relationship between organizational factors and job performance - Zeb, Ali (2020)
Employees’ job performance is a vital component of every organization especially Pakistan Telecom Company Limited (PTCL) since it has been facing issues of employees’ job performance for the last several years. Moreover, previous studies had shown that employees’ job performance may be caused by several organizational factors such as organizational culture, organizational justice, leadership and high-performance human resource practice (HPHR). However, it is still unclear how these factors (i.e. organizational culture, organizational justice & authentic leadership, HPHR) interact and affect desirable employees’ job performance. Therefore, this study aims to fill this gap by empirically evaluating the effects of organizational factors; organizational culture, organizational justice, authentic leadership on employee’ job at PTCL. Using contingency approach, HPHR was hypothesized to mediate these relationships. A quantitative research approach using cross-sectional survey design was used to collect data at PTCL. Respondents were selected using convenience sampling due to the inaccessibility to PTCL employees’ database. A total of 377 questionnaires were analyzed using SmartPLS 3.0. The findings revealed that clan culture and distributive justice influenced job performance via the partial mediating roles of selective staffing and extensive training. The market culture also influenced job performance by the partial mediating role of extensive training. The relational transparency has an impact on job performance by the partial mediating role of incentive reward. Also, balance processing influenced job performance by the partial mediating role of selective staffing. On the other hand, hierarchy culture, adhocracy culture, interactional justice, procedural justice, self-awareness, internalized moral perspective, employment security, and result-oriented appraisal were not significant predictors of job performance. The proposed model of job performance for PTCL would enable the PTCL management to develop strategies for high performing employees